Development Communication Sourcebook : Broadening the Boundaries of Communication - Mefalopulos, Paolo (Washington, DC : World Bank, 2012)
This Sourcebook illustrates how the emerging paradigm in development communication, focused on participation and two-way communication, constitutes a necessary element in order to avoid the mistakes of the past. It makes the case about the importance of incorporating communication practices into the policies and practices of development. It intends also to offer a broader conception of communication that would take into account other purposes and functions than the usual ones. The study claims that communication is not only about raising awareness, informing, persuading, or changing behavior. It is also about listening, exploring, understanding, empowering, and building consensus for change. This should resonate loud and clear for the reader. Two-way communication, used to understand, assess, explore, and facilitate decision making related to change, combined with the effective use of one-way communication approaches, has been proven to significantly enhance results and the sustainability of development initiatives. This Sourcebook is intended to provide a small contribution in further promoting the understanding and subsequent adoption of such practices, in any sector of intervention. To sum up, these are the two key messages of this publication: (1) two-way communication, when used from the onset of a development initiative, is not only a useful but also a necessary ingredient to enhance development initiatives and avoid the failures of the past, and (2) two-way communication should be applied professionally by specialists familiar with the rich body of knowledge and the diverse range of methods, techniques, and tools of development communication.